Облачная платформа разработки интеллектуальных систем поддержки принятия решений - Прохоров, Александр Валерьевич; Прохоров, Валерий Павлович; Матюшко, Анастасия Олеговна (НТУ "ХПИ", 2015)
Предлагается облачная платформа в рамках моделей PaaS и SaaS, которая обеспечивает поддержку всех этапов по разработке интеллектуальных систем поддержки принятия решений, их адаптацию для решения прикладных задач в любых предметных областях, хранение баз знаний и данных в облачных датацентрах, предоставление доступа к интеллектуальным системам как к сервисам удалённо через веб-интерфейс. Рассмотрены сценарии использования, решаемые задачи. Представлена структура платформы разработки интеллектуальных систем поддержки принятия решений.

Proposed cloud platform within the PaaS model and SaaS, which provides support for all phases of the development of intelligent decision support systems, adapting them for applications in all subject areas, storage of knowledge bases and data in cloud data centers, providing access to intelligent systems as services remotely via the web interface. Considered scenarios, tasks. The structure of the development platform of intelligent decision support systems is provided. The platform provides relief to development, testing, deployment and maintenance of intelligent systems without investment in infrastructure and software environment; increasing the degree of intellectualization and adapting existing information systems to changes in goals and objectives.
Cloud development platform of intelligent decision support systems
Keywords: интегрированная среда разработки; онтологии; инфраструктура; программная среда; intelligent systems; cloud platform